Male victimization of women Covered in Society’s Expectation in Razia Sultana Khan’s Seduction: The Perspective of Seven Building Tasks of Language - Nurvita Wijayanti (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2017)
Living in the society’s expectation is like we are forced to do what they want us to do and it is in the circle of hell. At one time, we need society as the means to communicate and be a natural human being. At the other hands, its culture and custom destroy ourselves especially those who have sexist culture and custom. This Bangladesh short story titled Seduction is one of the representatives of society that has sexist culture. It tells about a young girl who is forced to marry at the young age and becomes the object of her husband’s sexual trinket. What the writer wants to emphasize is the way the author named Razia Sultana Khan describe the treatment and the culture through Paul Gee’s seven language blocks’ perspective. The result of the discussion is that this short story, indeed, contains some of the seven building blocks that are significance, activities, identities, relationships, politics, connections and sign systems and knowledge.